Factors predicting classroom WTC in English and French as foreign languages among adult learners in Spain - Barrios-Espinosa, María Elvira; Acosta-Manzano, Irene (Sage, 2021)
This study aimed to identify associations and predictors of willingness to communicate (WTC) of adult foreign language (FL) learners and whether they are contingent upon the FL being learned. To this end, our research investigated learner variables associated with WTC in adult FL learners of English and of French in an under-researched field of WTC studies in Spain. More specifically, the following variables were studied: gender, age, level of multilingualism, perceived relative standing in the class, language proficiency, teacher’s use of the FL in class, out-of-class foreign language use (OCFLU) and the two emotions of foreign language enjoyment (FLE) and foreign language classroom anxiety (FLCA). Of the 9 independent variables examined, FLCA and language proficiency were found to be predictors of the WTC of both English and French language learners; additionally, enjoyment was found to be a predictor of WTC of learners of English as a foreign language (EFL) and OCFLU, of learners of French as a foreign language (FFL). Our findings indicate that the construct of WTC needs to be further studied as research may produce dissimilar results depending on the instructional setting, population and foreign language. Pedagogical implications for language teaching practices seeking to enhance adult FL learners’ WTC were also drawn from the study results.
Keywords: Inglés - Estudio y enseñanza; English as a foreign language; French as a foreign language; Adult learners; Willingness to communicate (WTC)